Perbandingan Pendidikan; Pemahaman Simbolis Dan Substantif PAI Di Madrasah Dan PAI Di Sekolah Umum - Moh. Wardi; Ismail Ismail; Ali Makki (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
Madrasah and schools have the same vision, mission and goals, namely the organizers of education in order to educate the life of the nation. Both of these institutions each have their own uniqueness and characteristics, because of their different backgrounds and histories. Competition and competition between educational institutions are still finding things that are unfair and cause polemics with each other. Even though the status and pos of the madrasa is the same as the school as the Joint Decree of the Minister of Religion of the Republic of Indonesia, the Minister of Home Affairs of the Republic of Indonesia, and the Minister of Education and Culture, and SKB 3 Minister Number 06/1975.037/U/1975, and Number 36/1975 about improving the quality and quality of education in madrasas. The main points and substance of the referred SKB are first, that the recognition of diplomas at madrasah graduates can have a value equivalent to the recognition of public school diplomas and equivalent. Secondly, graduates / madrasah alumni can continue their studies to public schools and those who are on a higher level. And third, students in the madrasa can transfer to public schools of the same level. If we understand the difference between madrasa and school, it is only limited to textual understanding, it will lead us to a simple understanding and be trapped in mere symbolic understanding. So when these differences can be created at school, the difference between madrasa and other schools will disappear.